The Ixodid Ticks (Acari: Ixodidae) of Southern Africa - Horak, Ivan G. (Springer International Publishing, 2018)
This is a comprehensive work summarizing the current state of knowledge of the biology of the hard ticks (Acari: Ixodidae) of Southern Africa (South Africa, Namibia, Botswana, Swaziland, Lesotho and Maputo Province, Mozambique). It provides an overview of the history of tick research in Southern Africa and the evolution of our knowledge of the ticks' distribution and biology, as well as the methods used to determine tick distribution, abundance and host preference. The morphologies of most of the tick species known to occur in Southern Africa are described and illustrated, and their distributions are described and mapped in relation to the biomes of the region. The known hosts for each tick species are listed, and the tick's host preferences are discussed. Information on most species life cycle in the laboratory and the field, and their seasonal occurrence, is summarized. The diseases of animals and humans transmitted or caused by each tick species are summarized in relation to tick ecology. Aspects of the biology of the major hosts relevant to tick infestations are described, and extensive tick/host and host/tick lists are provided for each country.